An Internship Concerning Exploration and Oppotunities in the Marine and Yachting Operation - Gupta, Ansh (ATLAS SkillTech University, 2025)
This report summarises the experiences, learning, and insights during my internship as an Operations Intern at West Coast Marine Yacht Services Pvt. Ltd which is one of the prominent companies in the Indian yachting industry. The internship really set practical one sought myself exposed interplay during the implementation of various functions, starting from the staffing and preparatory time of upcoming activity and ending with the provision of some operations to the process concourse and its assessment. This is an extensive and well-rounded report, the framework of which follows the structure of the Indian os well as global yachting industry, the company’s internal framework with respect to persons under consideration, my contributions and the general sense of gain from the training.
Project Report on An Internship Concerning Exploration and Oppotunities in the Marine and Yachting Operation (2023-2025) Under the Guidance of Prof. Omkar Pandharkame
Keywords: Opeartions; Training